When private information settles the bill: Money and privacy in Google's market for smartphone applications - Michael E. Kummer; Patrick Schulte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We shed light on a money-for-privacy trade-off in the market for smartphone applications ("apps"). Developers offer their apps cheaper in return for greater access to personal information, and consumers choose between lower prices and more privacy. We provide evidence for this pattern using data on 300,000 mobile applications which were obtained from the Android Market in 2012 and 2014. We augmented these data with information from Alexa.com and Amazon Mechanical Turk. Our findings show that both the market's supply and the demand side consider an app's ability to collect private information, measured by their use of privacy-sensitive permissions: (1) cheaper apps use more privacy-sensitive permissions; (2) installation numbers are lower for apps with sensitive permissions; (3) circumstantial factors, such as the reputation of app developers, mitigate the strength of this relationship. Our results emerge consistently across several robustness checks, including the use of panel data analysis, the use of selected matched "twin"-pairs of apps and the use of various alternative measures of privacy-sensitiveness.
urn:nbn:de:bsz:180-madoc-409586
Keywords: D12; D22; L15; L86; 330; Privacy; Mobile Applications; Android; Permissions; Supply and Demand of Private Information